Overcrowding and possible solutions for a busy gynecological emergency department: a hospital-based setting - Qazi, Mahvish; Saqib, Najmus; Gupta, Sachin (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: The objective of this study is to determine the trends of patients presenting in Obstetrics and Gynecology emergency department and to identify possible solutions. Methods: This retrospective hospital record-based study was conducted at Government Medical College Jammu, Jammu and Kashmir, India from the department of Gynecology and Obstetrics and comprised data of all patients presenting to the emergency department between 1st January 2018 to 31st December 2018. Patients were assessed in terms of demographic features, presenting complaints, admission types (urgent, non-urgent), referral from other hospitals or coming from home. The total number of patients admitted and the number of patients sent home was also recorded. Results: A total of 1,46,366 patients were analyzed retrospectively. Out of which 63,004 (43.05%) were send home from the OPD while 83,362 (56.95%) presented to the emergency department. Of them, 49,383 (59.24%) were discharged straight away from the ED after emergency treatment and care while 339,79 (40.76%) were admitted. Out of 339,79 patients, 24,932 (73.37%) stayed in the emergency whereas 9047 (26.63%) admitted into different wards for elective procedures. Majority of the patients 26,098 (89.92%) came from home and 2927 patients (10.08%) were referred from other hospitals. Labour pains 7833 (31.42%) was the most common presentation. Trauma was the reason for admission in 112 (0.45%) patients out of 29025. 971 (3.89%) patients presented with gynecological problems. 4093 (14.10%) patients presented with non-urgent indications. Rest of all patients presented with indications which were categorized as urgent and were admitted. All data was analysed using SPSS version 20. Conclusions: To reduce the overcrowding in the emergency department and improve quality of obstetrics and gynecological services, Inpatients and Outpatient departments at primary and secondary care levels need to be strengthened. Patients with non-urgent problems should be provided adequate care at primary and secondary health care centers.